Biochemical Changes in Two Barley Genotypes Inoculated With a Beneficial Fungus Trichoderma harzianum Rifai T-22 Grown in Saline Soil - Gupta, Sneha Vinay Kumar; Smith, Penelope M. C.; Natera, Siria H. A.; Roessner, Ute (Frontiers in Plant Science, 2022)
One of the most important environmental factors impacting crop plant productivity is soil salinity. Fungal endophytes have been characterised as biocontrol agents that help in plant productivity and induce resistance responses to several abiotic stresses, including salinity. In the salt-tolerant cereal crop barley (Hordeum vulgare L.), there is limited information about the metabolites and lipids that change in response to inoculation with fungal endophytes in saline conditions. In this study, gas chromatography coupled to mass spectrometry (GC-MS) and LC–electrospray ionization (ESI)–quadrupole–quadrupole time of flight (QqTOF)-MS were used to determine the metabolite and lipid changes in two fungal inoculated barley cultivars with differing tolerance levels to saline conditions. The more salt-tolerant cultivar was Vlamingh and less salt tolerant was Gairdner. Trichoderma harzianum strain T-22 was used to treat these plants grown in soil under control and saline (200 mM NaCl) conditions. For both genotypes, fungus-colonized plants exposed to NaCl had greater root and shoot biomass, and better chlorophyll content than non-colonized plants, with colonized-Vlamingh performing better than uninoculated control plants. The metabolome dataset using GC-MS consisted of a total of 93 metabolites of which 74 were identified in roots of both barley genotypes as organic acids, sugars, sugar acids, sugar alcohols, amino acids, amines, and a small number of fatty acids. LC-QqTOF-MS analysis resulted in the detection of 186 lipid molecular species, classified into three major lipid classes - glycerophospholipids, glycerolipids, and sphingolipids, from roots of both cultivars. In Cultivar Vlamingh both metabolites and lipids increased with fungus and salt treatment while in Gairdner they decreased. The results from this study suggest that the metabolic pathways by which the fungus imparts salt tolerance is different for the different cultivars.